2008
DOI: 10.1055/s-2007-965160
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Ultrasound for the Golfer Shoulder

Abstract: Although golf is a popular sport amongst different age groups, it can result in injury, usually from overuse and from poor technique. The shoulder is a commonly affected site, with the lead shoulder (e.g., the left shoulder in the right-handed golfer) most vulnerable to injury. In our present study, we used ultrasound to analyze if a hyperlaxity of the lead shoulder was present. In total, 33 asymptomatic golf-players were investigated by questionnaire, clinical examination and static, as well as dynamic ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It was observed that recreational golfers do not show any dorsal instability, leading to the presumption that shoulder instability is related to professional golfers, only (Michael et al, 2008).…”
Section: Ball Address and Backswingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that recreational golfers do not show any dorsal instability, leading to the presumption that shoulder instability is related to professional golfers, only (Michael et al, 2008).…”
Section: Ball Address and Backswingmentioning
confidence: 99%
“…Dorsal shoulder instability and secondary impingement are often attributed to the fact that the backswing phase involves a maximum adduction of the trailing arm at the end of this phase (Hovis et al, 2002). It was reported that recreational golfers do not show any dorsal instability, suggesting that shoulder instability is seen in professional golfers only (Michael, Kuhn, Yildirim, Eysel, & Ko ¨nig, 2008).…”
Section: Swing Phases and The Incidence Of Injuriesmentioning
confidence: 99%
“… 29 Last, this technique allows the physician to promptly observe the “dynamic centering” of the humeral head inside the joint. As such, it represents an indirect ultrasonographic sign of functional neuromotor control of the shoulder, that is, the balance between internal and external rotator muscles 31–34 …”
Section: Posterior Aspectmentioning
confidence: 99%
“…As such, it represents an indirect ultrasonographic sign of functional neuromotor control of the shoulder, that is, the balance between internal and external rotator muscles. [31][32][33][34]…”
Section: Retroacromial Window (Aber Maneuver) Techniquementioning
confidence: 99%
“…As a random sample, the papers published in the January (No.1) issues of 2008, 2009, and 2010 were looked up to ascertain the month of acceptance, of eFirst publication, and of publication in printed version (issue 1 of each respective year). For 2008, 15 papers were included [2,5,11,18,20,21,24,26,27,29,30,33,34,37,38] ; 11 papers were published in the no. 1 issue of 2009 [1, 3, 6 -9, 12, 13, 19, 28, 35] ; the respective issue in 2010 included 12 papers [4, 10, 14 -17, 22, 23, 25, 31, 32, 36] .…”
Section: Positive Development Of the Processing Time -Time Span Betwementioning
confidence: 99%